The biology of Promerops cafer with special reference to the role of the nectar and satellite insect fauna of Protea repens in the reproductive cycle - Mostert, David P (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1974.